Implementasi ICT Sebagai Sistem Pendukung Keputusan Dalam Meningkatkan Efektivitas Manajemen Organisasi - Fikry Jie Riefa Ananda; Muhammad Irwan Padli Nasution (CV. SINAR HOWUHOWU, 2026)
The way businesses handle data, make choices, and accomplish strategic objectives has changed significantly as a result of the advancement of information and communication technology (ICT). The purpose of this study is to examine how using ICT as a decision support system (DSS) might increase organizational management's efficacy. The approach is a review of prior research findings and a variety of scholarly sources concerning the use of ICT in organizational decision-making. The findings demonstrate that the use of ICT in decision support systems helps to improve the speed, precision, and caliber of managerial judgments. ICT also boosts organizational competitiveness, operational efficiency, and interdepartmental coordination.